The study of professional identity of the PH.D. Students with Grounded theory method (Case study: PH.D. Students of social sciences in Iran 2016 – 2017) - A. Vedadhir; A. Sedighian Bidgoli; Gh. Jafari (Taḥqīqāt-i Farhangī-i Īrān, 2017)
Accepted doctoral students in the social sciences in Iran have doubled since 86-87Ta94-95T. This increase, apart from road infrastructure in the humanities and social sciences research. Lack of job opportunities, particularly in the field of professional and social sciences in Iran, the importance of assessing the status of the actors involved in the field of social sciences has doubled. The study examines how a professional identity among doctoral students in the social sciences has been discussed. The research method used was based on grounded theory. The basic subject of study called the phenomenon of professional identity has been uneven.The study examines how a professional identity among doctoral students in the social sciences has been discussed. The research method used was based on grounded theory. The true measure of its regular professional knowledge, job definition in line with the social sciences and the mental representation and reproduction of knowledge is not consistent with the approach favored relationship.